Knowledge Mapping of COVID-19 and Asthma/Allergic Rhinitis: A Visual and Bibliometric Analysis - Chen Y; Song C; Wang J; Cao Y; Lu Y; Han X (Journal of Asthma and Allergy)
Yanni Chen,1,2,* Chenfei Song,3,* Jiaqin Wang,2 Yang Cao,4 Yueting Lu,5 Xinmin Han6 1First Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 2Shanghai Baoshan District Youyi Street Community Health Service Center, Shanghai, People’s Republic of China; 3Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 4Shanghai Putuo District Shiquan Street community Health Service Center, Shanghai, People’s Republic of China; 5Shanghai Yangpu District Yanji Community Health Service Center, Shanghai, People’s Republic of China; 6Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinmin Han, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China, Email 15195996828@163.comObjective: Numerous studies have highlighted a link between COVID-19 and respiratory allergic conditions such as asthma and allergic rhinitis (AR). Despite the growing volume of research, there remains a notable gap in the form of a comprehensive bibliometric analysis that consolidates the findings on this association. This study aims to fill that gap by systematically exploring how asthma and AR interact with COVID-19.Methods: By using the Web of Science Core Collection, we selected publications from January 2020 to October 2024 that related to COVID-19 and asthma/AR. Analysis tools such as VOSviewer and CiteSpace were employed to perform network mappings and citation analyses, focusing on co-authorship networks, keyword co-occurrences, and citation impacts to understand the research dynamics and collaborative patterns within this field.Results: A collection of 553 publications was obtained, revealing an upward trend in research volume over the study period. The United States, China, and the United Kingdom were predominant in the research output, demonstrating extensive international collaborations. The study highlighted key areas of impact, such as the influence of asthma types on COVID-19 severity and the protective effects of specific treatments like inhaled corticosteroids and biologics. Emerging trends identified included the significance of socioeconomic factors and obesity in disease outcomes, as well as evolving strategies in vaccination and interventions.Conclusion: This bibliometric analysis highlights the significant role of global research in exploring the interactions between COVID-19 and asthma/AR. It points out the reported safety and effectiveness of COVID-19 vaccines for these conditions and acknowledges the challenges in vaccine uptake among minority and socioeconomically disadvantaged groups. The study also identifies unique risks for children and obese patients during the pandemic and underscores the need for increased international collaboration and more comprehensive clinical trials, to evaluate the efficacy of treatments like inhaled corticosteroids and biologics.Keywords: COVID-19, asthma, allergic rhinitis, bibliometric analysis, vaccine